Aplikasi Media Pembelajaran IPA Untuk MI Berbasis Augmented Reality - Bagus Dwi Yulianto; Rohman Dijaya; Mochamad Alfan Rosid (Infotek: Jurnal Informatika dan Teknologi, 2023)
MI Darul Huda is one of the Islamic elementary schools iAn the Jabon District, Sidoarjo Regency. The learning process still uses books and 2-dimensional pictures. Therefore, supporting facilities and infrastructure are needed, educational media is one example of learning media that facilitates students in the interactive learning process so that students are not bored and students can see real 3D objects. Increase student interest in the learning process using augmented reality technology. Augmented reality (AR) scientific-based educational media application was developed for Michigan International University to assist student learning. The Multimedia Design and Development Life Cycle (MDLC) is a 6 stage process (concept, design, materials assembly, assembly, testing, distribution), used in this approach or study. Using markers, augmented reality science learning media applications can provide three-dimensional visuals of object markers. The research and testing all led to the conclusion that Android serves as a viable platform for using Augmented Reality as a scientific education tool. AR successfully displays 3D objects based on marker objects, features are able to run according to functions and information on science subject matter can be understood. The best results in displaying objects are from a distance of 10-15 cm with standard light conditions